تحسين كفاءة شبكة مياه الشرب باستخدام نموذج EPANET حالة الدراسة (المنطقة الواقعة بين شارعي 8-آذار والكورنيش الغربي) - سلمان هناء; شيبان ساميه; يوسف مايا (Latakia University Journal -Engineering Sciences Series, 2019)
تحسين كفاءة شبكة مياه الشرب باستخدام نموذج EPANET حالة الدراسة (المنطقة الواقعة بين شارعي 8-آذار والكورنيش الغربي) مايا يوسف هناء سلمان ساميه شيبان بهدف تحسين كفاءة شبكة مياه الشرب في المنطقة والواقعة بين شارع 8آذار والكورنيش الغربي في مدينة اللاذقية التي تتميز بفروق كبيرة في المناسيب. تم استخدام برنامج EPANET الذي وضعته وكالة الحماية البيئية الأميركية USEPA من أجل المحاكاة الهيدروليكية للشبكة. تمت الاستعانة بكروكي للمنطقة وذلك لمعرفة مناسيب العقد وميول الخطوط. تم تقدير الغزارات العقدية بناء على الاستهلاك المائي للسكان. نتيجة مراقبة الاستهلاك في المنطقة واعتمادا على معطيات مديرية المياه وضع نمط معدلات الاستهلاك المائي على مدار اليوم وذلك للقيام بالتحليل الهيدروليكي لفترة زمنية طويلة باستخدام برنامج WaterCAD الذي يعتمد على النموذج الرياضي EPANET أظهرت النتائج انخفاض قيم الضغوط في 25 % من عقد الشبكة وهي العقد ذات المناسيب العالية حيث كانت الضغوط أقل من bar1 وبالنسبة للسرعات في الأنابيب فكانت أعلى قيمة 3.3 m/s في خط الجر الرئيسي وأصغر قيمة 0.02 m/s في الخطوط المتفرعة ذات النهايات الميتة. للتحقق من نتائج المحاكاة الهيدروليكية تم اللجوء إلى تتبع تراكيز الكلور الحر المتبقي على أرض الواقع وأظهرت محاكاة نمذجة جودة المياه أن أكبر عمر للمياه في الشبكة 50 ساعة والتي يبلغ عندها تركيز الكلور الحر القيمة 0.14 mg/l. لهذه الغاية تم إدخال معامل تحلل كلور قيمته 0.01d-1 والذي تم استنتاجه من خلال معايرة النموذج اعتمادا على القياسات الحقلية. تم اقتراح إنشاء خزان عالي وتمت محاكاة السيناريو الجديد في برنامج WaterCAD . لوحظ تحسن كبير في قيم الضغوط bar (4.8-2.85) وهي ضمن المجال المسموح. كما تحسنت قيم السرعات وأصبحت ضمن المجال من m/s (-2.20.47). لوحظ أن إضافة جرعة كلور إلى خزان المصدر بمقدار 0.2mg/l قد عمل على رفع تراكيز الكلور الحر المتبقي ضمن الشبكة مما يعزز جودة مياه الشرب ويحافظ على السلامة العامة. This paper aims at improving the efficiency of the drinking water network in the region between the 8th Azar Street and the Western Corniche in the city of Latakia, which is characterized by large differences in the levels. For that, the EPANET program developed by the US Environmental Protection Agency was used for the hydraulic simulation of the network. A site plan drawing has been used for the area to know the nodes levels and lines slope. Water flow in the nodes was estimated by monitoring the water consumption in this area. Based on the data of the (Water Authority), the pattern of water consumption rates was developed throughout the day to perform the hydraulic analysis for an extended period of time using the WaterCAD program based on the mathematical model EPANET, The results showed a reduction in pressure values in almost 25% of the network nodes, which are high-level nodes, where pressures were less than 1 bar. It showed also that water velocities in the network are ranging from 3.3 m/s in the main carrier line and 0.02 m/s in branching lines with dead ends. In order to validate the results of the hydraulic model, the residual free chlorine concentrations in the network were recorded at the field. The hydraulic model showed also that the largest water age in the network is 50 hours, at which the free chlorine concentration was 0.14 mg/L, and so, chlorine decay rate in the hydraulic model was updated to 0.01 day-1. This value was derived by calibrating the model based on the field measurements. It was proposed to create an elevated tank in the highest area of the network. This scenario was checked using WaterCAD software. The model results showed a significant improvement in the pressure values (2.85-4.8) bar which still within the allowable pressure range. Also, the velocity values were improved (0.47 -2.2) m/s. and the model showed that the addition of chlorine to the source tank by 0.2 mg/L increased the free chlorine concentrations in the network, what enhances the quality of drinking water and maintains the public safety.